VIRTUAL DEBATE IN EFL CLASSROOM: IMPACTS ON THE STUDENTS’ SPEAKING SKILL - Asriani Zuriah Harahap; Yulianus Harefa; M. Syafie’ie Siregar (ELP (Journal of English Language Pedagogy), 2021)
The main objective of this study was to describe the implementation of virtual debate in teaching speaking and to identify students’ speaking skill improvement after being taught by using virtual debate. To achieve the objective of the study, a qualitative descriptive method was used. The data was gathered through debate speeches given by eight debaters from SMA Muhammadiyah 9 Kualuh Hulu. It includes the Opening Government team (Prime Minister and Deputy Prime Minister), the Opening Opposition team (Leader of the Opposition and Deputy Leader of the Opposition), Closing Government (Government Member and Government Whip), and Closing Opposition (Closing Government and Closing Whip) taken from the practicing debate for 4 meetings. The data in this study were the transcription of debate activities. The steps taken in this analysis were collecting data by transcribing debate speeches into text, identifying improvisation and fluency, and concluding the analysis. The results showed that the improvisation and fluency of the Prime Minister, Deputy Prime Minister, Leader of the Opposition, Deputy Leader of the Opposition, Government Member, Government Whip, Closing Government, and Closing Whip were in medium levels from the beginner level. In both improvisation and fluency levels, debate speeches showed considerable improvisation and fluency.